1(x-(-1))=7

Simple and best practice solution for 1(x-(-1))=7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1(x-(-1))=7 equation:



1(x-(-1))=7
We move all terms to the left:
1(x-(-1))-(7)=0
We move all terms containing x to the left, all other terms to the right
1(x-(-1))=7

You can always share this solution

See similar equations:

| 8n-14n-3n^2+2=0 | | 8=w.2+2 | | -3(x-(-1))=-3 | | 10-8x=-15+11x | | 12y-8+4y+y-2=0 | | 5x+3(.5x)=3,000 | | -3(-3y+5)=-60 | | 25=-0,003x2+0,0638x+40 | | 12y-8y+4y+y-2=0 | | -2(z+4)=-37 | | 15x+5(.5x)=6067 | | 6x+36=-3(x+9) | | -6(u-2)=-8u+14 | | 2w+9=9(w+8) | | 30-5z=8(9z+7) | | C/4+76=4b | | 4x+9x-8x=6+4 | | 8x-90=-2 | | 6+1/2x=x(2) | | 3/2a+1/4=5/8 | | v^2+15v+59=0 | | 5y×2y=-24 | | 3-x/5=10 | | -4(w-9)=3w+8 | | -2=8w | | -9y+20=-2(y-3) | | 5(x+2)=6x+3x-14 | | -3(y+4)=5y-28 | | 10k(k+2)=k-6 | | -45b=-39b | | d+12/6=20/8 | | F(t)=1,500(1.045) | | j*7=56 | | v*7=28 | | 7*v=48 | | v*7=48 | | 2*i=18 | | c*5=35 | | 4a+a=20;a= | | 1/4-10=7;b= | | 1/3(x+8)=10 | | 2x+25=32 | | 7w-38=-4(w-7) | | v2=-84 | | 4(v+4)=-8v+40 | | 7z-9=-3 | | -3y-9=2y=3 | | 4=20d | | y=3=4y-18 | | 31=5(y+8)+4y | | 30=6v+3(v-5) | | 4(w+8)+4w=16 | | x-(x*0.08)=3270191.37 | | x-(x*0.08)=896023.87 | | 2^(x-2)-11^(-10x)=0 | | 6w+7(w+3)=-31 | | -3=5(y-7)+3y | | 6(n+7)=2(21+3) | | 52=v+8v | | 9=10w-w | | 6x-2=5×-7-3× | | 5x-21=29 | | 2(m+13)=3m+3 | | 190=2l+2l+3 | | 27=1w-6w |

Equations solver categories